Land use change in a Mediterranean metropolitan region and its periphery: assessment of conservation policies through CORINE Land Cover data and Markov models - Ruiz-Benito, Paloma; Cuevas, J.A.; Bravo, R.; Garcia-del-Barrio, Jose Manuel; Zavala, Miguel Angel (Forest Systems, 2010)
Sustainable territorial management requires reliable assessment of the impact of conservation policies on landscape structure and dynamics. Euro-Mediterranean regions present a remarkable biodiversity which is linked in part to traditional land use practices and which is currently threatened by global change. The effectiveness of one-decade conservation policies against land use changes was examined in Central Spain (Madrid Autonomous Community). A Markov model of landscape dynamics was parameterized with CORINE Land Cover information and transition matrices were obtained. The methods were applied in both protected and unprotected areas to examine whether the intensity and direction of key land use changes —urbanisation, agricultural intensification and land abandonment— differed significantly depending on the protection status of those areas. Protected areas experienced slower rates of agricultural intensification processes and faster rates of land abandonment, with respect to those which occurred in unprotected areas. It illustrates how simple mathematical tools and models —parameterized with available data— can provide to managers and policy makers useful indicators for conservation policy assessment and identification of land use transitions.